Aggression in pigtailed macaque (Macaca nemestrina) breeding groups affects pregnancy outcome - Ha, James (2011)
Past research has shown that aggressive behaviors can affect female reproductive outcome in non-human primate captive breeding programs. In this study, aggressive behaviors were recorded in a colony of pigtailed macaque monkeys (Macaca nemestrina) and related to pregnancy outcome. For twenty-two weeks, behavioral data were collected from nine breeding groups, consisting of zero to one male (some males were removed after a cycle of conceptions for husbandry reasons) and four to eight females. Observations included all occurrences of eleven aggressive behaviors during 15-minute observation sessions, one to three times a week. Mean weekly aggression levels during the study period were determined for each group, as well as for each pregnancy. Aggression data were summarized with Principal Components Analyses (PCA). Results indicate that pigtailed macaque aggression falls into five distinctive categories: warn, engage, threaten, pursue, and attack. Breeding groups differed in their levels of aggression, even after controlling for group size, presence of a sire, and group stability. Levels of the five aggression categories were found to affect the probability that a pregnancy ended in either a natural birth of a live infant, a clinical intervention producing a live infant, or a nonviable outcome. The predictive value of aggression was significant when clinical interventions were included as possible reproductive outcomes, Behavioral observation of captive groups could identify “risk” conditions affecting pregnancy outcome and the requirement for clinical intervention.